Bahasa Inggris - Caecielia Makaginsar; Meta Maulida Damayanti; Yuniarti; Siska Nia Irasanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Background: Good knowledge and behaviours are crucial to prevent coronavirus disease (COVID-19) transmission in boarding school communities during the pandemic.Objective: To evaluate the relationship between sociodemographic characteristics, knowledge, and behaviours to prevent COVID-19 among students in an Islamic boarding school. Methods: A descriptive cross-sectional study was conducted in March 2021 at the Manarul Huda Islamic Boarding School on 39 students who met the inclusion criteria. Sampling was employed using the total sampling technique. Variables analysed were students’ age, education level, knowledge, and behaviour on COVID-19 prevention as measured using a closed questionnaire. Data were then analysed univariately using frequency distribution and bivariate using the Chi-Square (χ2) and Fisher’s Exact test. Results were considered significant if the p-value was < 0.05.Results: No significant relationships were found between age and knowledge of COVID-19 (p = 0.97); education level and knowledge of COVID-19 (p = 0.619); age and behaviours to prevent COVID-19 transmission (p = 0.136); and education level and behaviours to prevent COVID-19 transmission (p = 0.399) among of the Islamic boarding school students. In contrast, knowledge was significantly (p = 0.035) linked with behaviours to prevent COVID-19 transmission among students.Conclusion: There is a relationship between knowledge and behaviours in preventing COVID-19 among students. However, no relationship was found between demographic characteristics of age and educational level and knowledge and behaviours to prevent COVID-19 in our study participants.